Determining the performance of HR-GNSS and RTS geodetic techniques for Structural Health Monitoring - Topal, Güldane Oku; Akpınar, Burak (Advances in Geodesy and Geoinformation, 2024)
This study investigates the effectiveness of geodetic methods in Structural Health Monitoring (SHM), focusing on the utilization of the High-Rate Global Navigation Satellite System (HR-GNSS) and Robotic Total Station (RTS) for monitoring structural movements. Experiments were conducted on a horizontal single-axis shake table to simulate various frequencies and amplitudes. Data were analyzed using time series and Fast Fourier Transform (FFT) techniques to evaluate the performance of geodetic measurement methods in SHM studies Two applications were conducted using a single-axis shake table. In the first, the table oscillated at 0.25 Hz frequency and 20 mm amplitude, while data from a GNSS receiver on the upper table underwent processing with the TRACK module of GAMIT/GLOBK software using the kinematic post-process (KPP) GNSS technique. In the second, the reflector on the shake table moved through eight oscillations at various amplitudes and frequencies, monitored automatically with a LEICA TPS1200 RTS. Time series and FFT analyses were performed on all application data to determine oscillation frequencies and amplitudes. Method accuracy was assessed by comparing these values with data from the shake table’s high-precision position sensor (Linear Variable Differential Transformer-LVDT). Results showed good agreement between HR-GNSS measurements and LVDT data, with a -1.6mm amplitude difference for KPP GNSS. Additionally, RTS measurements accurately determined frequency values, with amplitude differences ranging from 0.2 mm to 6.5 mm. Root Mean Square Error (RMSE) values for eight RTS tests, covering frequencies between 0.25-0.50 Hz and amplitudes between 4.5-73.4 mm, varied from 2.1mm to 6.3mm, reflecting performance variability across different conditions.